Dado in expansion - Szidon, Amarante (Napredak, 2025)
This essay reflects on the legacy of Montenegrin artist Dado (Miodrag Đurić, 1933–2010), who spent most of his career and life in France, in a context where new narratives in art history emerge giving more visibility to non-Western artists. Through the complex and fertile bond between the East and the West cultures, the importance of the landmark retrospective of paintings of the artist at the SASA Gallery in 2024, and the restoration of his in situ masterpiece, the Orpellières, his “Guernica in color”, the author shows Dado’s extreme contemporaneity. New insights, not only in art history, but also in aesthetics, philosophy and literature, show the fascinating echo of Dado’s work in our times.